2013
DOI: 10.1515/ijdhd-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Objective outcome evaluation of a leadership and intrapersonal development subject for university students

Abstract: A quasi-experimental study with an experimental group (n = 195) and a control group (n = 71) was conducted to examine the effectiveness of a leadership and intrapersonal development subject at The Hong Kong Polytechnic University. Results showed that there were no significant differences between the two groups in terms of gender ratio, age, and background family characteristics. Analyses of covariance controlling for pretest differences between the two groups revealed that students in the experimental group ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Findings of the present study add to the previous results by showing the beneficial effects of a leadership course on promoting the holistic development among the firstyear Hong Kong college students [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The results of the current study showed that participants scored higher in several composite and subscale measures over the course of the semester.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Findings of the present study add to the previous results by showing the beneficial effects of a leadership course on promoting the holistic development among the firstyear Hong Kong college students [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The results of the current study showed that participants scored higher in several composite and subscale measures over the course of the semester.…”
Section: Discussionsupporting
confidence: 79%
“…Multiple evaluation strategies including objective outcome evaluation, subjective outcome evaluation, process evaluation, and qualitative evaluation were used to assess the effects of this subject. The evaluation findings were generally positive in these two pilot studies [17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 79%
“…There are some negative Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 6/15/15 2:58 PM Table 3 responses such as "boring" and "inadequate time to teach the materials". These findings are highly similar to the first piloting exercise and second piloting exercise [21][22][23][24][25]. Nevertheless, it is noteworthy that there are some negative responses recorded.…”
Section: Discussionsupporting
confidence: 82%
“…Compared to the control participants, students who had joined the program showed more positive holistic development and lower levels of adolescent risk behavior [35,36]. Further supporting evidence was found for a leadership subject based on positive youth development constructs offered at The Hong Kong Polytechnic University [37][38][39][40][41][42]. All these suggest that this kind of adolescent development curriculum is worth implementing in university settings.…”
Section: Discussionmentioning
confidence: 96%